2019
DOI: 10.3892/mmr.2019.10613
|View full text |Cite
|
Sign up to set email alerts
|

miR‑488 negatively regulates osteogenic differentiation of bone marrow mesenchymal stem cells induced by psoralen by targeting Runx2

Abstract: It has been previously reported that psoralen, one of the active ingredients in Psoralea corylifolia, could induce osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs), suggesting its potential to treat osteoporosis. Additionally, runt-related transcription factor 2 (Runx2) is a transcription factor that plays vital roles in BMSC osteogenic differentiation. However, whether and how microRNAs (miRNAs/miRs) modulate osteogenic differentiation induced by psoralen have not yet been examined, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 24 publications
1
23
0
2
Order By: Relevance
“…ELISA assay was performed to estimate the expression of IL-6, IL-18, IL-1b, TNF-a, IL-10. **P < 0.01 compared with control group; ## P < 0.01 compared with HG group;^P < 0.05 compared with HG + psoralen group;^^P < 0.01 compared with HG + psoralen group downregulation of miR-488 [28]. In another study of Lei Jin et al, psoralen increased chemotherapeutic sensitivity in patients with gastric cancer through upregulating miR-196a-5p [29].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…ELISA assay was performed to estimate the expression of IL-6, IL-18, IL-1b, TNF-a, IL-10. **P < 0.01 compared with control group; ## P < 0.01 compared with HG group;^P < 0.05 compared with HG + psoralen group;^^P < 0.01 compared with HG + psoralen group downregulation of miR-488 [28]. In another study of Lei Jin et al, psoralen increased chemotherapeutic sensitivity in patients with gastric cancer through upregulating miR-196a-5p [29].…”
Section: Discussionmentioning
confidence: 93%
“…If other miRNAs were involved in the regulation process of psoralen in DN remains to be investigated. When psoralen was used to treat other diseases, different miRNAs were involved [28][29][30]. According to a study of Yongquan Huang et al, psoralen improved the osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs) by the Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When psoralen was used to treat other diseases, different miRNAs were involved [30][31][32]. According to a study of Yongquan Huang et al, psoralen improved the osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs) by the downregulation of miR-488 [30]. In another study of Lei Jin et al, psoralen increased chemotherapeutic sensitivity in patients with gastric cancer through upregulating miR-196a-5p [31].…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al found that miR-488 was downregulated in bone marrow mesenchymal stem cells (BMSCs) following treatment with psoralen. Runx2 was found to be a potential target of miR-488 (Huang et al, 2019). It has been suggested that the targeting of Runx2 by miR-488 may participate in osteogenic differentiation after treatment with psoralen.…”
Section: Other Actionsmentioning
confidence: 99%